2006
DOI: 10.1016/j.bbabio.2006.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Identification of amino acid residues essential for reconstitutive activity of subunit IV of the cytochrome bc1 complex from Rhodobacter sphaeroides

Abstract: A region of subunit IV comprising residues 77-85 is identified as essential for interaction with the core complex to restore the bc(1) activity (reconstitutive activity). Recombinant subunit IV mutants with single or multiple alanine substitution at this region were generated and characterized to identify the essential amino acid residues. Residues 81-84, with sequence of YRYR, are required for reconstitutive activity of subunit IV, because a mutant with these four residues substituted with alanine has little … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Indeed, the recent structural studies of a supercomplex formed from complexes I and III indicate that the matrix part of complex III is required for its association with complex I (14). The matrix region of Complex III may also be important for stabilization of the complex itself as bc 1 complexes without core proteins are generally less stable and have lower activity (15). If the interaction between the matrix enzymes and the bc 1 complex exists, this region would be a good choice for the contact.…”
mentioning
confidence: 99%
“…Indeed, the recent structural studies of a supercomplex formed from complexes I and III indicate that the matrix part of complex III is required for its association with complex I (14). The matrix region of Complex III may also be important for stabilization of the complex itself as bc 1 complexes without core proteins are generally less stable and have lower activity (15). If the interaction between the matrix enzymes and the bc 1 complex exists, this region would be a good choice for the contact.…”
mentioning
confidence: 99%
“…Indeed, the recent structural studies of a supercomplex formed from complexes I and III indicate that the matrix part of complex III is required for its association with complex I (14). The matrix region of Complex III may also be important for stabilization of the complex itself as bc 1 complexes without core proteins are generally less stable and have lower activity (15). If the interaction between the matrix enzymes and the bc 1 complex exists, this region would be a good choice for the contact.…”
mentioning
confidence: 99%
“…When purified recombinant subunit IV was added to the three-subunit core complex, the bc 1 activity was restored to the level of the wild-type complex, indicating that recombinant subunit IV can properly assemble into the cytochrome bc 1 complex [8]. The availability of reconstitutively active, three-subunit core complex and recombinant subunit IV enables us to use an in vitro reconstitution approach to identify the amino acid residues of subunit IV involved in interaction with the core complex [9, 10]. Residues 81–84, with a sequence of YRYR [10], and residues 86–109, which comprise the only transmembrane helix in subunit IV [9], are essential.…”
Section: Introductionmentioning
confidence: 99%
“…The availability of reconstitutively active, three-subunit core complex and recombinant subunit IV enables us to use an in vitro reconstitution approach to identify the amino acid residues of subunit IV involved in interaction with the core complex [9, 10]. Residues 81–84, with a sequence of YRYR [10], and residues 86–109, which comprise the only transmembrane helix in subunit IV [9], are essential. It has been suggested that subunit IV is incorporated into the bc 1 complex through its transmembrane helix and then interacts with the core subunits through residues 81–84 to restore the bc 1 activity to the level of the wild-type complex [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation